2019
DOI: 10.5798/dicletip.661256
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Dose Ketamine Infusion on Postoperative Acute and chronic Pain after Thoracotomy

Abstract: Objective: The aim of this study was to investigate the effects of a perioperatively administered low dose of ketamine on postoperative acute, chronic pain following thoracotomy. Methods: Forty patients with ASA I-III and aged between 18 and 65 years were included in the study. Patients were randomly divided into two groups. Group I (n=20) was administered a ketamine 0.5 mg.kg -1 bolus followed by a 2 mcg.kg -1 .dk -1 infusion for 24 hours before the incision. Group II (n=20) was given normal saline at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Overall, nine articles were found that matched the search criteria (Figure 1). Nine articles (13,(22)(23)(24)(25)(26)(27)(28)(29) comprising 556 patients were selected for meta-analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, nine articles were found that matched the search criteria (Figure 1). Nine articles (13,(22)(23)(24)(25)(26)(27)(28)(29) comprising 556 patients were selected for meta-analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Mean Difference with 95% CI: −2.75 [−4.14, −1.36], p-value = 0.0001). In subgroup analysis, the model favors the ketamine group on POD 1 and POD 1-3, but these results are sensitive to the exclusion of studies by Pehlivan et al (29) and Michelet et al (13), respectively (see Figure 4).…”
Section: Cumulative Opioid Consumption During the First 3 Pods (Mg Of...mentioning
confidence: 92%